2018
DOI: 10.1007/s10900-018-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sex-Specific Distribution of Cardiovascular Risk Factors in University Students in an Urban–Rural Environment of the Democratic Republic of the Congo

Abstract: A recent qualitative study on health promotion in non-communicable diseases in Sub-Saharan University students suggested sex differences in knowledge and beliefs concerning a healthy lifestyle. However, the extent to which this is reflected in sex-specific distribution of cardiovascular risk factors among Sub-Saharan African students have not been fully evaluated. The objective of this study was to assess the prevalence and the sex-specific distribution of some modifiable cardiovascular risk factors among stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…This was corroborated by a study among medical students of the University of Makerere in Uganda, where cardiovascular risk factors with the highest prevalence was alcohol consumption with 31.7% of the sample indicating regular alcohol consumption [ 21 ]. Similar results were also reported at the university of Kikwit in the Democratic Republic of Congo with 53.1% of alcohol consumption among the sample [ 17 ]. This high alcohol consumption could be explained by the fact that students think that alcohol makes it easier to meet other people, relaxes their social inhibitions, and helps them have more fun.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This was corroborated by a study among medical students of the University of Makerere in Uganda, where cardiovascular risk factors with the highest prevalence was alcohol consumption with 31.7% of the sample indicating regular alcohol consumption [ 21 ]. Similar results were also reported at the university of Kikwit in the Democratic Republic of Congo with 53.1% of alcohol consumption among the sample [ 17 ]. This high alcohol consumption could be explained by the fact that students think that alcohol makes it easier to meet other people, relaxes their social inhibitions, and helps them have more fun.…”
Section: Discussionsupporting
confidence: 87%
“…A time-series study conducted in Cameroon from 2009 to 2012 among 2,726 young students indicated a prevalence of hypertension of 6.3% [ 16 ]. A similar result was reported in the Democratic Republic of Congo; the prevalence of hypertension was estimated at 7.6% among 780 students of the university of Kikwit between January and March 2016 [ 17 ]. In nine other low-and-middle income countries of Asia (Indonesia, Laos, Myanmar, Philippines, Thailand and Vietnam) a study among 4,649 university students found that 6.7% of them had hypertension, and 19.0% had pre-hypertension [ 18 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The prevalence of prehypertension observed in our study is of concern, particularly among Christian and Muslim males, considering the young age of the students. Several studies have shown that the prevalence of prehypertension is often higher in men than in women, which could be due to differences in hormonal activity during early life [ 31 , 32 ]. In addition, in our study it also coincides with a higher prevalence of overweight status.…”
Section: Discussionmentioning
confidence: 99%